Nine Open Arms - Lindelauf, Benny, 1964- (Enchanted Lion Books, 2014)
The eccentric, motley Boon family moves into an abandoned house on the outskirts of a Dutch town in the 1930s in an attempt to launch a cigar-making business venture, but they encounter hauntings of the house's past residents and a variety of obstacles to their efforts.